(untitled) (Kinesiology, 2022)
A low physical fitness and incorrect technique could result in muscle strength imbalance and poor dynamic/ static balance in handball players. This study aimed to evaluate the muscular and functional performance of lower limbs in female handball athletes. Twelve female handball athletes performed isokinetic tests at 60°/s, 120°/s, 180°/s, and 240°/s for the knee’s extensor and flexor muscles and functional tests for lower limbs. Regarding the muscular performance, there were no differences between the limbs in the knee’s muscles’ peak torque, while the values of the conventional ratio were below the recommended. With respect to the functional tests, no significant changes were observed. On the other hand, the composite score of the Y-Balance test demonstrated values below the suggested. Overall, the results showed that young female handball athletes had symmetry between the limbs in the muscular and functional performance; however, there was a tendency to muscle imbalance (hamstrings weaker than quadriceps), and dynamic balance deficits that might increase the risk of musculoskeletal injury. Key words: young female athletes, team handball, muscle strength, functional evaluation